Investigating the possible neurological side effects follow the COVID-19 vaccine - Atalu, Abolfazl; Sadeghieh-Ahari, Saeed; Khademmasjedi, Haleh (International Journal of Basic & Clinical Pharmacology, 2023)
Background: With the widespread of COVID-19 vaccination around the world, there are many case reports which referred to the neurological complications following vaccination. However, due to the lack of more information about this, especially in our country Iran, the aim of this study was to investigate the possible neurological side effects of the COVID-19 vaccine in patients. Methods: This cross-sectional study was conducted on 1046 people injecting various types of COVID-19 vaccines, including Sinopharm, AstraZeneca, Sputnik V, CovIran-Barekat, Covaxin, SpikoGen, and PastoCovac plus, who were registered in the health system due to vaccine complications. These people were evaluated in terms of the overall incidence rate of neurological complications, types of neurological complications, and the relationship between the occurrence of neurological complications and the type of vaccine. Results: Of all patients, 589 (56.3%) were female and 457 (43.7%) were male, and most of them were from the age group of 60 years and older (43.8%). 247 people (23.6%) had neurological complications that most of them related to the headache (16.6%). Conclusions: The results of this study showed that the neurological side effects associated with the covid-19 vaccination were in mild level and most of them were seen in AstraZeneca vaccine and so, in line with the recommendation of the European medicines agency, the injection of this vaccine should be done with caution.